Managing nonperforming loans in Bangladesh. - Dey, Barun Kumar (Metro Manila, Philippines Asian Development Bank, 2019)
The ratio of NPLs to total loans in Bangladesh as of 2017 was 9.3%, which is high compared to other countries in Asia and the Pacific. Data show that NPLs in Bangladesh have been rising and falling in previous decades, but they have been increasing again in recent years. The brief presents reform measures, regulatory solutions, and risk mitigation techniques that several countries in Asia and Europe applied to address NPLs following the 1997 financial crisis. Policy recommendations for Bangladesh are based on international best practices that focus on strengthening corporate governance, legal frameworks, and banking regulations to mitigate risks associated with loans.
Keywords: Financial institutions -- Bangladesh; Banks and banking -- Bangladesh; Electronic books